2018
DOI: 10.1186/s12913-018-3762-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Xpert MTB/RIF and decentralized care on linkage to care and drug-resistant tuberculosis treatment outcomes in Johannesburg, South Africa

Abstract: BackgroundIn 2011, South Africa improved its ability to test for rifampicin-resistant TB (RR-TB) by introducing GeneXpert MTB/RIF. At the same time, the South African National TB program adopted a policy decentralized, outpatient treatment for drug resistant (DR-) TB. We aim to analyze the impact of these changes on linkage to care and DR-TB treatment outcomes.MethodsWe retrospectively matched adult patients diagnosed with laboratory-confirmed RR-TB in Johannesburg from 07/2011–06/2012 (early cohort) and 07/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 21 publications
5
33
1
1
Order By: Relevance
“…Treatment delays were, thus, related more to inadequate community awareness about TB disease and available services, and distrust of the public sector, agreeing with several studies in sub-Saharan Africa (57)(58)(59). Approachability in several SSA countries were hampered by poor provider knowledge and attitudes, poor referral systems and patient tracking, as in our study (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionsupporting
confidence: 85%
“…Treatment delays were, thus, related more to inadequate community awareness about TB disease and available services, and distrust of the public sector, agreeing with several studies in sub-Saharan Africa (57)(58)(59). Approachability in several SSA countries were hampered by poor provider knowledge and attitudes, poor referral systems and patient tracking, as in our study (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionsupporting
confidence: 85%
“…reported in similar patient cohorts from South Africa [18,19] and Zambia [20], where the majority of patients were co-infected with HIV. However, the better treatment outcomes in the current study may be due to potential selection bias of excluding patients treated at primary health centres.…”
Section: Plos Onementioning
confidence: 65%
“…This compares well with the median delay-time of 13 days (IQR 7-28) and 15 days (IQR 8-23) reported in Johannesburg and in the Eastern Cape in South Africa, respectively. In a Cape Town study, Cox et al found a relatively shorter median time to treatment initiation of eight days [9][10][11][12] . In these studies, time to treatment initiation was measured from sputum submission at the laboratory while we measured it from the availability of a positive Xpert MTB/RIF assay result with rifampicin resistance.…”
Section: Discussionmentioning
confidence: 99%